Berberine enhances the function of db/db mice islet β cell through GLP-1/GLP-1R/PKA signaling pathway in intestinal L cell and islet α cell - Wu, Wenbin; Xia, Qingsong; Guo, Yujin; Wang, Hongzhan; Dong, Hui; Lu, Fuer; Yuan, Fen (Frontiers in Pharmacology, 2023)
Background: The evidence on berberine stimulating the secretion of GLP-1 in intestinal L cell has been studied. However, few research has explored its role on generating GLP-1 of islet α cell. Our experiment aims to clarify the mechanism of berberine promoting the secretion of GLP-1 in intestinal L cell and islet α cell, activating GLP-1R and its downstream molecules through endocrine and paracrine ways, thus improving the function of islet β cell and treating T2DM.Methods: After confirming that berberine can lower blood glucose and improve insulin resistance in db/db mice, the identity maintenance, proliferation and apoptosis of islet cells were detected by immunohistochemistry and immunofluorescence. Then, the activation of berberine on GLP-1/GLP-1R/PKA signaling pathway was evaluated by Elisa, Western blot and PCR. Finally, this mechanism was verified by in vitro experiments on Min6 cells, STC-1 cells and aTC1/6 cells.Results: Berberine ameliorates glucose metabolism in db/db mice. Additionally, it also increases the number and enhances the function of islet β cell. This process is closely related to improve the secretion of intestinal L cell and islet α cell, activate GLP-1R/PKA signaling pathway through autocrine and paracrine, and increase the expression of its related molecule such as GLP-1, GLP-2 / 14 1R, PC1/3, PC2, PKA, Pdx1. In vitro, the phenomenon that berberine enhanced the GLP-1/GLP-1R/PKA signal pathway had also been observed, which confirmed the results of animal experiments.Conclusion: Berberine can maintain the identity and normal function of islet β cell, and its mechanism is related to the activation of GLP-1/GLP-1R/PKA signal pathway in intestinal L cell and islet α cell.